2020
DOI: 10.1080/19415257.2020.1744684
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of mentoring for new teachers

Abstract: She researches professional learning, in particular informal learning and mentoring and is also interested in children and young people's rights. Rachel is a co-convenor of the Open Learning network of the European Educational Research Association (network 6) and is on the governing body of the Scottish Educational Research Association. She is a Senior Fellow of the Higher Education Academy and is a member of the Scottish Community Learning and Development Standards Council. Rachel previously had a varied care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 55 publications
0
27
0
3
Order By: Relevance
“…Team teaching or coteaching is frequently included within induction of new teachers. Team teaching might be exploited further as a means to stimulate collaborate inquiry in support of collaborative professional learning (Schnellert and Butler, 2020 [56]). Examples of its use beyond the early years of teaching mentioned during the OECD study visit included a school leader focusing a staff meeting on learning more about team teaching and opportunities for staff dialogue.…”
Section: Emergence Of Collaborative Learning Practices Within and Across Schoolsmentioning
confidence: 99%
“…Team teaching or coteaching is frequently included within induction of new teachers. Team teaching might be exploited further as a means to stimulate collaborate inquiry in support of collaborative professional learning (Schnellert and Butler, 2020 [56]). Examples of its use beyond the early years of teaching mentioned during the OECD study visit included a school leader focusing a staff meeting on learning more about team teaching and opportunities for staff dialogue.…”
Section: Emergence Of Collaborative Learning Practices Within and Across Schoolsmentioning
confidence: 99%
“…The importance of the relationship quality might be even more accentuated during the induction phase of a teacher's career (Stanulis and Russell 2000, Mitchell et al 2019, Squires 2019), during which a yearlong (or even longer) and more in-depth relationship between the mentor teacher and the beginning teacher develops. As research has already indicated, the quality of the mentoring relationship is likely to crucially impact the learning opportunities of newly qualified teachers, as well as teacher attrition and retention (Long et al 2012, Shanks et al 2020.…”
Section: Resultsmentioning
confidence: 99%
“…It is also likely that less frequent formal and, in particular, informal interactions will occur if positive relationships cannot be established. Moreover, the quality of mentoring is frequently regarded as an important factor in reducing the attrition rate of newly qualified teachers during the induction phase (Odell and Ferraro 1992, Long et al 2012, Shanks et al 2020. Thus, the quality of the mentor-mentee relationship is not only regarded as an important resource for optimal learning opportunities in the practicum, but it also functions as a significantly influential factor regarding attrition and retention in the early years of teachers' careers.…”
Section: Relationship Quality Between Student Teachers and Their Mentmentioning
confidence: 99%
“…In English, induction is a complex concept covering NQTs' learning processes, need for support, vulnerability, special activities and programs. Although most induction programs include mentoring, the authors of this book sometimes use the term "induction and mentoring", mostly to emphasize the importance of mentoring in induction ( Attard- Langdon, Alexander, Ryde & Baggetta, 2014;Shanks et al, 2020). We refer to the explanation of the term mentoring below.…”
Section: Inductionmentioning
confidence: 99%